Juan López Sánchez en Francia - Dr. Pedro García-Guirao (Cahiers de Civilisation Espagnole Contemporaine)
This work explores the scantly studied Spanish anarchist exile that followed the Spanish Civil War and lasted until Francisco Franco’s death and, arguably, beyond. The article is built around the controversial case of Juan López Sánchez (1900-1972) –one of the four anarchists that became ministers during the Second Spanish Republic. In what follows, the work traces the panoramic historical, geographical and ideological journey of Juan López Sánchez mainly through his correspondence, with particular attention to his brief French exile.